Management of innovations and conflicts of interests on the level of the sector of economy (by example of the transport complex) (Путеводитель предпринимателя, 2020)
In article the basic directions of the correlation between innovation process and the effectiveness of the conflicts of interests' management are considered. The factor-components of the conflict of interest that influence the innovation process in the positive as well as in the negative way are analyzed. The ways to minimize the negative influence of the conflicts of interests and its management towards successful innovation process development are proposed.